Cell Therapy for Refractory Angina: A Reappraisal - Beatrice Bassetti; Patrizia Nigro; Valentina Catto; Laura Cavallotti; Stefano Righetti; Felice Achilli; Paolo Scacciatella; Corrado Carbucicchio; Giulio Pompilio (Hindawi Limited, 2017)
Cardiac cell-based therapy has emerged as a novel therapeutic option for patients dealing with untreatable refractory angina (RA). However, after more than a decade of controlled studies, no definitive consensus has been reached regarding clinical efficacy. Although positive results in terms of surrogate endpoints have been suggested by early and phase II clinical studies as well as by meta-analyses, the more recent reports lacked the provision of definitive response in terms of hard clinical endpoints. Regrettably, pivotal trials designed to conclusively determine the efficacy of cell-based therapeutics in such a challenging clinical condition are therefore still missing. Considering this, a comprehensive reappraisal of cardiac cell-based therapy role in RA seems warranted and timely, since a number of crucial cell- and patient-related aspects need to be systematically analysed. As an example, the large variability in efficacy endpoint selection appears to be a limiting factor for the advancement of cardiac cell-based therapy in the field. This review will provide an overview of the key elements that may have influenced the results of cell-based trials in the context of RA, focusing in particular on the understanding at which the extent of angina-related endpoints may predict cell-based therapeutic efficacy.